PERAN BIMBINGAN KONSELING DAN PENDIDIKAN AGAMA ISLAM (PAI) : PENERAPAN DAN SOLUSI DI MAN 2 PALEMBANG - Marlia, Ani; Fadhilah, Nur Ainun; Pertiwi, Monica; Hasan Yusuf, Muhammad; Wulandari, Nova Suci; Sari, Sella Mustika; Pratama S, Muhammad Randi; Ani, Safitri (SIGNIFICANT : Journal Of Research And Multidisciplinary, 2023)
The purpose of the research is to find out the role of counseling guidance and Islamic Religious Education (PAI): Application and Solutions at MAN 2 Palembang. Islamic religious education supports knowledge about religious science while counseling guidance is tasked with perfecting it by shaping a person's personality by understanding himself first. This article uses qualitative research methods that are complemented by observation research techniques where the author interviews directly combined with library techniques, the author searches from sources in the form of books, articles and research results that have related titles. At MAN 2 Palembang there are several negative activities that are often carried out by students in the form of arriving late, using cellphones while studying and skipping class hours all of this is due to the influence of advances in technology and science. Islamic religious education and counseling guidance which acts as a direction giver makes decisions in the form of first reprimanding students, secondly conducting personal meetings with students, and finally consulting with student guardians, students and counselors. The method used is quite effective seeing the many changes that can be seen